Total Maximum Daily Loads and Agricultural BMPs in Florida - Brian J. Boman; Kelly T. Morgan; Kati W. Migliaccio; Sandra Guzman; Haimanote K. Bayabil (EDIS)
This document is ABE 362, one of a series of the Agricultural and Biological Engineering Department, UF/IFAS Extension.  This update with Sandra Guzman, and Haimanote Bayabil, April 2019.